Tax compliance costs of small and medium enterprises in Malaysia: policy implications - Pope, Jeffrey; Jabbar, Hijattulah (School of Economics and Finance, Curtin Business School, 2008)
Tax compliance costs often fall heavily on small and medium enterprises (SMEs). The international tax literature exhibits a similar pattern of fixed costs effect whether measured for a specific tax or overall business taxes. In Malaysia, the government SME focus is often restricted to general business and finance-related issues. However, the issue of the tax compliance burden is yet to materialise explicitly. This paper discusses this SME tax compliance burden, relevant international and Malaysian compliance cost estimates and challenges for Malaysian SMEs. The paper concludes by indicating the tax policy challenges facing the government, particularly for SMEs.